2020
DOI: 10.1002/lno.11404
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of iron and light limitation on the molecular physiology of the Southern Ocean diatom Fragilariopsis kerguelensis

Abstract: The polar diatom Fragilariopsis kerguelensis is ubiquitous in Southern Ocean waters and is a major responder to iron fertilization, encountering large gradients in iron concentrations and light availability. We performed a comparative transcriptomic analysis of F. kerguelensis grown under varying iron and light conditions in order to investigate the molecular underpinnings that may explain its physiological response to iron and light limitation. Low iron reduced growth rates more than low light, but there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 124 publications
1
14
1
Order By: Relevance
“…We cross‐compared our findings to explore whether we can obtain insights into the individual environmental factors we manipulated (Table 2). The proteomic trends we observed in the photosystem I pathway in the control mesocosm are corroborated by previous work (Moreno et al 2020). We also detected flavodoxin and chloroplast ferredoxin dependent NADH oxidoreductase proteins in some taxa.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We cross‐compared our findings to explore whether we can obtain insights into the individual environmental factors we manipulated (Table 2). The proteomic trends we observed in the photosystem I pathway in the control mesocosm are corroborated by previous work (Moreno et al 2020). We also detected flavodoxin and chloroplast ferredoxin dependent NADH oxidoreductase proteins in some taxa.…”
Section: Discussionsupporting
confidence: 92%
“…Others detected that phytoplankton photosynthetic competency and photosynthetic apparatus proteins decrease under low Fe alone (Wu et al 2019;Moreno et al 2020); we observed the opposite trend. In our manipulation, five environmental drivers were altered, whereas in experiments against which we compare our results, one or two drivers were amended.…”
Section: Trendcontrasting
confidence: 84%
See 1 more Smart Citation
“…However, T. oceanica maintained high growth rates (~80% of the rate in iron-replete conditions) in low-iron media that restricted the growth of T. weissflogii to ~20% of its iron-replete growth rate. Two studies confirmed similar streamlining in F. kerguelensis and P. granii, polar diatoms that are abundant in the Southern Ocean and the Arctic Ocean, respectively ( Cohen et al , 2018a ; Moreno et al , 2020 ). In P. granii , the gene encoding PSI subunit IV ( PSAE ) was almost 4-fold more highly expressed under iron-replete conditions, and protein levels were more abundant by 35-fold compared with their levels under conditions of iron limitation ( Cohen et al , 2018a ).…”
Section: Low Iron Quota Diatoms Regulate the Amount Of Iron Required mentioning
confidence: 60%
“…3 ). In a recent study, Moreno et al (2020) investigated the response of three isoforms of PETE to iron in this species, and found that only two were significantly over-represented under low-iron conditions. In T. oceanica, which encodes PETE together with two functional copies of PETJ , the relative expression of plastocyanin was sensitive to iron status, while two genes encoding cytochrome c 6 were weakly but constitutively expressed ( Lommer et al , 2012 ).…”
Section: Low Iron Quota Diatoms Regulate the Amount Of Iron Required mentioning
confidence: 99%